SISTEM INFORMASI ABSENSI BERBASIS WEBSITE PADAPT MARGA SEJAHTERA BERSAMATAMA - Amalia Rosdiana (2022)
Attendance is an activity that is used to measure the level of discipline of a person in an organization or company. Currently, several companies are starting to implement a work from home system due to the increasing COVID-19 pandemic. As a result of this, attendance activities that were originally carried out manually at the office must now be replaced so that employees can still take attendance when working from home. So, a temporary substitute was made, namely the Google form, but the use of the Google form is also not effective because the data can be filled in by anyone. So, research was conducted to create a website-based attendance information system using GPS (Global Positioning System) as a substitute for the Google form attendance method. This study uses the waterfall method as a reference for the system to be built. The results of this study are in the form of a website-based application that can be used by employees to carry out attendance activities and provides a convenience for the (Human Resource) HR team to recap employee attendance reports.